Spherical polyelectrolyte nanogels as templates to prepare hollow silica nanocarriers: observation by small angle X-ray scattering and TEM. Issue 76 (12th October 2017) - Han, Haoya; Li, Li; Tian, Yuchuan; Wang, Yunwei; Ye, Zhishuang; Yang, Qingsong; Wang, Yiming; von Klitzing, Regine; Guo, Xuhong
Abstract : Hollow silica nanoparticles were prepared through generating a silica layer in spherical polyelectrolyte nanogels, which consisted of a solid core of polystyrene and a shell of crosslinked poly(acrylic acid), followed by removing the core via solvent dissolution. Abstract : Hollow silica nanoparticles were prepared through generating a silica layer in spherical polyelectrolyte nanogels (SPN), which consisted of a solid core of polystyrene (PS) and a shell of crosslinked poly(acrylic acid) (PAA), followed by removing the PS core via solvent dissolution. Small angle X-ray scattering (SAXS) in combination with TEM were employed to observe SPN, silica–polymer composite, and hollow silica nanoparticles. It was confirmed that SAXS is a powerful method to monitor the generation of silica layer in SPN. The density and thickness of generated silica layer in SPN were found to be tunable by controlling the crosslinking density of the templates. The porous structure and pH sensitivity of silica layer allowed the obtained hollow silica to be ideal carriers for controlled drug delivery.